Features of social intelligence of cadets trained in institutions of higher education with specific learning conditions - S. V. Kharchenko (Law and Safety)
It has been noted that the data on the development of the abilities of students’ social intelligence during their studies in higher education institutions, which are presented in the literature, are ambiguous and need to be clarified.